How efficient is the implementation of structural funds committed to enhancing ICT adoption in SMEs? - Carla Oliveira Henriques; Clara Viseu (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
We evaluated the execution of the operational programs (OPs) committed to encouraging the adoption of information and communication technologies (ICTs) in small and medium-sized enterprises (SMEs). To achieve this goal, we employed a novel three-stage weighted Russel directional distance (WRDD) data envelopment analysis (DEA) model in conjunction with stochastic frontier analysis (SFA), which considers indicators officially mandated by the European Union (EU) and environmental factors, to evaluate 51 OPs from 16 EU countries. All in all, we concluded that by removing the environmental factors, about 30% of the OPs (16) reached an efficient procedural performance against 20% (10). The OP more frequently viewed as a benchmark regardless of the environmental factors is "Multi-regional Spain-ERDF" that remains robustly efficient within 5% and 10% tolerances. Without the removal of the environmental factors, the "number of operations supported" is the indicator that requires more attention from management authorities (MAs), whereas with their removal one-third of the OPs need to further reduce the "eligible costs decided" and improve "eligible spending". According to our findings, more developed regions and a higher rate of ICT specialists seem to be related to an underuse of ERDF funds dedicated to boosting ICT in SMEs. These findings might be related to the administrative burden and the lack of ability of SMEs to deal with the various procedures for applying for and implementing European Regional Development Fund (ERDF) projects. Overall, it is critical to provide further support that simplifies administrative procedures and addresses SMEs' specific requirements.
Keywords: C6; C1; O3; M1; 650; SMEs; ICT; ERDF; EU regions; WRDD model